Il tabarchino - Autelli, Erica; Caria, Marco (Linguistik Online, 2025)
The present contribution aims at illustrating the complex history of Tabarchin, a diatopic variety spoken in the Sulcis Archipelago, both in Carloforte and Calasetta, brought to the area by Genoese people (mostly from Pegli) who settled in Tabarca in Tunisia mainly for coral fishing. Secondly, the main vowel and consonantic phonemes and some morphosyntactic and semantic features of Tabarchin will be shown, illustrating at the same time the shared spelling proposed in 2001. Finally, the last section will annnounce the most significant projects for the dissemination of Tabarchin, a historical minority variety unfortunately not recognised by the national law 482/1999.